DEVELOPMENT OF MICE AND HAMSTER EMBRYOS IN KSOMAA AND HECM-6 MEDIUM - Rosadi, Bayu; Agus Setiadi, M; Sajuthi, Dondin; Boediono, Arief (Jurnal Veteriner; Vol 9 No 4 (2008))
The purpose of the present study was to investigate the viability of mice and hamster embryos developed in Kalium Simplex Optimized Medium amino acid (KSOMaa) and Hamster Embryo Culture Medium-6 (HECM-6) medium. Female DDY mice were superovulated by injection i.p. of 5 IU Pregnant Mare Serum Gonadotropine (PMSG) and 5 IU Human Chorionic Gonadotropine (hCG) in 48 h interval, hamster (Phodopus campbelli) injected by 2.5 IU PMSG and 2.5 IU hCG 48 h later. Then females were mated with fertile males. Eight-cell embryos were recovered at day 3 after natural mating. The mice embryos were cultured in KSOMaa+5% NBCS (New Born Calf Serum) (T1) and HECM-6+5% NBCS (T2), the hamster embryos were cultured in KSOMaa+5% NBCS (T3) and HECM-6 + 5% NBCS (T4) for further development at 37oC in a humidified atmosphere of 5% CO2 in air for 48 h. The examinations were replicated five times. The T1 embryos developed to compact morulla and early blastocyst 100% (140/140), 92.1% (129/140) to blastocyst and expanded blastocyst, and 22.9% (32/140) became hatching/hatched. The T3 reached 100% (60/60) to compact morulla and early blastocyst, 85.0% (51/60) blastocyst, and 48.3% (29/60) expanded blastocyst, no embryo observed hatching/hatced. The T2 embryos had more expanded blastocyst than T3 (P<0.05), hatching/hatched rate higher than T1 and T3 but lower than T4 (P<0.05). Shortly, KSOMaa enable to support 8-cell stage mice and hamster embryo, but the hamster embryo developed lower at expanded blastocyst stage. HECM-6 is more appropriate than KSOMaa to support 8-cell mice embryos development and suitable to develop 8-cell stage hamster embryos.
Keywords: embryo, medium, mice, hamster